The coast-to-coast murders [compact disc, unabridged] - Patterson, James, 1947-; Barker, J. D. (Jonathan Dylan), 1971- (Hachette Book Group, 2020)
LA detective Dobbs and FBI agent Gimble race against time and across state lines to stop a deeply deranged killer whose dark, twisted MO is outside the range of logic or experience.